PENGEMBANGAN MEDIA LITERASI SAINS (MELISA) BERBASIS INTERAKTIF CONSTRUCT 2 PADA MATA PELAJARAN IPAS KELAS V DI SDN SINGOPADU TULANGAN - Hidayat, Arif Nur; Murni, Arie Widya (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2024)
This research discusses the development of interactive science literacy media (Melisa) based on Construct 2 in class V science subjects at SDN Singopadu. This type of research uses the ADDIE development model which consists of 5 stages, namely Analysis, Design, Development, Implementation, Evaluation. This research aims to develop and measure the effectiveness of interactive scientific literacy media (Melisa) based on Construct 2. The media developed was validated by 2 validators. The results of the Melisa feasibility test research were based on the assessment: 1) The material expert validator obtained a percentage of 87.5% in the